Business education in Georgia: Challenges and opportunities - Tatiana Papiashvili (IBSU Scientific Journal (IBSUSJ), 2010)
Knowledge-based society rests on the knowledge triangle that refers to the interaction between research, education, and innovation. The presented paper discusses efficiency of business education in Georgia. SWOT analysis and a questionnaire held by the author show challenges and opportunities of business education in Georgia.
Keywords: 330; Knowledge-based society; business education; Georgia